2014
DOI: 10.1002/job.1979
|View full text |Cite
|
Sign up to set email alerts
|

Overqualification and counterproductive work behaviors: Examining a moderated mediation model

Abstract: SummaryThe current study examined the effect of employees' perceived overqualification on counterproductive work behaviors (CWBs). Building on person-job fit theory and prior research on such organizational phenomena, we conceptualized overqualification as a type of poor person-job fit. Drawing on the dual-process model, we further suggested that in processing their person-job misfit, overqualified employees might cognitively appraise themselves as less worthy organizational members and experientially feel ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
295
2
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(379 citation statements)
references
References 74 publications
(211 reference statements)
21
295
2
15
Order By: Relevance
“…First, our study counterproductive work behaviors (Liu et al, 2015, or creativity (Luksyte and Spitzmueller 2015). Further, consistent with a finding that job autonomy helps mitigate the negative consequences of perceived overqualification on job satisfaction especially in highly individualistic countries (Wu et al, 2014), our findings in Study 2 suggest usefulness of granting higher job autonomy in mitigating the negative consequences of perceived overqualification on employees' adaptive behavior.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 76%
See 2 more Smart Citations
“…First, our study counterproductive work behaviors (Liu et al, 2015, or creativity (Luksyte and Spitzmueller 2015). Further, consistent with a finding that job autonomy helps mitigate the negative consequences of perceived overqualification on job satisfaction especially in highly individualistic countries (Wu et al, 2014), our findings in Study 2 suggest usefulness of granting higher job autonomy in mitigating the negative consequences of perceived overqualification on employees' adaptive behavior.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 76%
“…It showed that people who feel overqualified experience decreased job satisfaction and low affective commitment Johnson 2000, McKee-Ryan et al, 2009) and have lower self-rated performance (Bolino and Feldman 2000). They are more likely to leave their jobs Bauer 2009, Maynard et al, 2006), and tend to engage in more counterproductive work behaviors (Liu et al, 2015, and fewer extra-role behaviors (Agut et al, 2009), although some inconsistent findings were also reported (see Liu and Wang 2012, for a review). For example, perceived overqualification has been found to positively relate to supervisor rated in-role performance (Holtom et al, 2002), organizational citizenship behavior (Chen 2009), overall job performance (Fine 2007, Fine andNevo 2008), and objective job performance indicators (Erdogan and Bauer 2009). This means that evidence regarding the relationship between perceived overqualification and job performance is, at best, inconclusive.…”
Section: Perceived Overqualificationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our findings add to the emerging evidence that reactions to injustice can be understood within the context of dual-process theories (e.g., Li et al, 2011;Liu et al, 2015;van den Bos, 2007). Second, our work extends emerging research on justice and rumination (e.g., Tripp & Bies, 2010;Wang et al, 2013).…”
Section: Theoretical Implicationsmentioning
confidence: 68%
“…OQ is negatively related to organizational commitment, wellbeing and job and career satisfaction, and positively related to job stress, counterproductive work behaviors, and turnover intentions (see for example Johnson & Johnson, 1992, 1996Liu et al, 2015;Luksyte et al, 2011;Maynard et al, 2006;McKee-Ryan & Harvey, 2011). However, much less is known about the antecedents.…”
Section: Introductionmentioning
confidence: 99%